The juridicization of doctrine at the expense of theological scholarship. The case of Mikayel Chamchian’s “Sheild of faith” - Nersessian, Nersess Revd․ (Տպարան Սրբոյ Յակոբեանց)
The rift between the Armenian Apostolic and Roman Catholic communities in Constantinople at the end of the 18th and first half of the 19th century- Formation of the Armenian millet system – Բան հրաւեր սիրոյ (‘An invitation to love’) - The failure to implement the acts of union with Rome in the 13th century - Fratres Unitores and the role of the Inquisition – Վահան Հաւատոյ (‘Shield of Faith’) – First abridged printed edition in comparison with a manuscript of the same in UCLA (Ms.Arm.14)- The theology of the ‘Shield of Faith’.
Keywords: Religion; Doctrinal Theology